Nivel de conocimiento de reanimación cardiopulmonar básico en el personal de salud de centro quirúrgico del hospital Víctor Lazarte Echegaray - Rodríguez Campos, Rosario del Pilar (2022)
To determine the level of knowledge of advanced Cardio Pulmonary Resuscitation (CPR) of the health personnel of the surgical center of the Lazarte Hospital. In such a way as to guarantee the greatest chance of survival after a Cardiorespiratory Arrest (CRP), since this depends directly on the quality and early initiation of Cardiopulmonary Resuscitation (CPR) maneuvers, as well as on the effectiveness of education and training. the periodic evaluation of the same, so that the knowledge and skills acquired by professionals can persist over time. Background: In 2015, approximately 350,000 adults in the United States experienced out-of hospital nontraumatic cardiac arrest (OHCA) and were cared for by emergency medical services (EMS) personnel. Despite recent advances, less than 40% of adults receive CPR initiated by medically inexperienced individuals and less than 12% use an automated external defibrillator (AED) prior to the arrival of EMS. After a period of significant improvement, survival to OHCA has stagnated since 2012. Method: A survey will be conducted of all health personnel working in the operating room of the Victor Lazarte Echegaray hospital to assess the level of knowledge of the CPR maneuvers. The sample selection will be carried out randomly until the sample size is completed with the health personnel who work in the surgical center service of the Víctor Lazarte Echegaray Hospital in Trujillo in the period of December 2020.